Sustainable development goals : law, theory and implementation - French, Duncan; Kotzé, Louis J.; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
Building on the previously established Millennium Development Goals, which ran from 2000-2015, the 2015 Sustainable Development Goals (SDGs) provide the UN with a roadmap for development until 2030. This topical book explores the associated legal and normative implications of these SDGs, which in themselves are not legally binding. The 17 goals and 169 targets of the SDGs cover areas as crucial as poverty reduction, climate change, clean water and access to justice. Combining both thematic and goal-specific analysis, expert contributors establish the relevance not just of international law, but also of a broader range of normative frameworks including constitutional norms, domestic regulatory law and human rights. Connecting the SDGs to wider debates in international law and politics, this book ultimately demonstrates that law has an important constitutive and instrumental role to play in both implemention and analysis. The first of its kind to offer a specific focus on the relationship between law and the SDGs, this much-needed book will prove invaluable for scholars in the field of international sustainable development. Its insightful observations will also provide food for thought for both related international organizations and national government officials.
1. Introduction / Duncan French and Louis Kotzé -- Part I General themes -- 2. The sustainable development goals, anthropocentrism and neoliberalism / Sam Adelman -- 3. The sustainable development goals: an existential critique alongside three new-millennial analytical paradigms / Louis Kotzé -- 4. SDGs and human rights: challenges and opportunities / Lynda Collins -- 5. Transformative shifts in the 2030 agenda for sustainable development / Graham Long -- 6. How the sustainable development goals promote a new conception of ocean commons governance / Nadia Castillo- Winckels -- Part II A selective analysis of particular goals -- 7. Gender and the sustainable development goals / Karen Morrow -- 8. International water law and SDG 6: mutually reinforcing paradigms / Owen Mcintyre -- 9. Good urban governance as a global aspiration: on the potential and limits of sustainable development goal 11 / Helmut Aust and Anel du Plessis -- 10. The environment and the SDGs: "We are on a road to nowhere" / Werner Scholtz and Michelle Barnard -- 11. Torn by (un)certainty - can there be peace between rule of law and other SDGs? / Niko Soininen -- 12. SDG 17: partnerships for the goals: cooperation within the context of a voluntarist framework / Duncan French and Nathan Cooper -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: udržitelný rozvoj; sustainable development; e-knihy online; e-books online